2016
DOI: 10.4184/asj.2016.10.4.630
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Percutaneous Lumbosacral Pedicle Screw Placement Using the Oblique Fluoroscopic View Based on Computed Tomography Evaluations

Abstract: Study DesignRetrospective.PurposeThis study aims to investigate the accuracy of the oblique fluoroscopic view, based on preoperative computed tomography (CT) images for accurate placement of lumbosacral percutaneous pedicle screws (PPS).Overview of LiteratureAlthough PPS misplacement has been reported as one of the main complications in minimally invasive spine surgery, there is no comparative data on the misplacement rate among different fluoroscopic techniques, or comparing such techniques with open procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In general, inaccurate PPS placement can cause potential postoperative neurological deficits [6][7][8][9]. Previous reports have indicated 4.7%-15% rates of inaccurate PPS placement; however, PPS placement is reported to be an effective technique with no difference in perforation rate from the standard open free-hand technique [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, inaccurate PPS placement can cause potential postoperative neurological deficits [6][7][8][9]. Previous reports have indicated 4.7%-15% rates of inaccurate PPS placement; however, PPS placement is reported to be an effective technique with no difference in perforation rate from the standard open free-hand technique [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported that MIS-TLIF can reduce tissue damage, blood loss, and postoperative pain compared with conventional TLIF [1][2][3][4]. In particular, PPS insertion can decrease damage not only to soft tissue but also to the superior facet joint because it is easier for surgeons to insert pedicle screws from the outside of the facet joint [14]. However, PPS insertion requires fluoroscopy or a navigation system.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have described the accuracy of percutaneous lumbar pedicle screw placement, especially when using the coax-ial fluoroscopic view. [10][11][12][13] In addition, the factors affecting the accuracy of pedicle screw insertion are unclear.…”
mentioning
confidence: 99%